Imaging of Cervical Lymph Nodes - KM, Keerthana; Kumar, Jyoti (Indographics, 2022)
The occurrence of cervical lymph node metastases is the single most important prognostic factor for head and neck malignancy. It directly influences the staging of tumors, selection of treatment plan, and patient prognosis. Various head and neck cancers have the propensity to spread to different nodal stations in the neck. CT/MRI is routinely used to evaluate the patient of head and neck malignancy. Knowledge of various cervical nodal levels, as well as the preferential drainage pattern of various sites of head and neck malignancies, can aid in accurate imaging interpretation.
Keywords: cervical lymph nodes; drainage pathways; nodal levels; nodal metastases; skip metastases